Estimation of a condition of electromagnetic relays a method of acoustic diagnostics in systems of railway automatics - Laguta, V. V.; Khizyakov, V. Y. (Science and Transport Progress, 2012)
The paper deals with methods of preliminary analysis of sound signals to extract stable features in classifying the relay used in railway automation systems. The algorithm of the description of a sound signal on the basis of these attributes is offered.